SELF-PERCEIVED HALITOSIS AND ORAL HYGIENE HABITS AMONG SCHOOL STUDENTS - A, Subashri; Priya, Jothi (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Aim: The aim of this study is to evaluate oral hygiene habits among school students and about the self-perceived halitosis. Objective: Brushing methods, oral hygiene aids, and use of products for good oral health will be evaluated. Background: A structured questionnaire consisting of 15 questions was administrated to 120 school students. The questionnaire was designed to evaluate the self-perception of halitosis, oral hygiene aids used, presence of caries, gingival bleeding, and dryness of mouth. Reason: Halitosis is characterized by unpleasant odor arising from the oral cavity. The prevalence of halitosis is not studied extensively among school students. Hence, this study is done to create awareness of oral hygiene habits among school students. Keywords: Oral health, Halitosis, Teeth, Brush, School students, Habits.